Developing Foreign Students' Communicative Competence. Review of T. Ye. Masytska Scientific Publication Ukrainian as a Foreign Language: Communication. Lutsk: Vezha-Druk, 2019 (Linguostylistic Studies, 2019)
Developing Foreign Students' Communicative Competence. Review of T. Ye. Masytska Scientific Publication Ukrainian as a Foreign Language: Communication. Lutsk: Vezha-Druk, 2019